IMPLEMENTASI DATA MINING UNTUK MENENTUKAN POLA PENJUALAN DENGAN MARKET BASKET ANALYSIS - Lestari, Novia; Gunawan, Refika Fitria (Fakultas Sains dan Teknologi UIN Imam Bonjol Padang, 2021)
The increasingly fierce competition in the business world lately has forced business actors to have the right strategy to increase their product sales, one of which is to determine sales patterns. However, along with the amount of sales transaction data that is carried out every day, it makes it difficult for business actors to analyze existing sales patterns. So we need a method that can help determine sales patterns from even large transaction data, one of which uses the Market Basket Analysis method which uses customer data that has been stored in the database to find new information in it. By utilizing the sales transaction data of consumers supported by the Market Basket Analysis method, it is possible to determine the right marketing tactics for business actors so as to increase sales